1-cos(6x)=3cos(2x)

Simple and best practice solution for 1-cos(6x)=3cos(2x) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 1-cos(6x)=3cos(2x) equation:


Simplifying
1 + -1cos(6x) = 3cos(2x)

Remove parenthesis around (6x)
1 + -1cos * 6x = 3cos(2x)

Reorder the terms for easier multiplication:
1 + -1 * 6cos * x = 3cos(2x)

Multiply -1 * 6
1 + -6cos * x = 3cos(2x)

Multiply cos * x
1 + -6cosx = 3cos(2x)

Remove parenthesis around (2x)
1 + -6cosx = 3cos * 2x

Reorder the terms for easier multiplication:
1 + -6cosx = 3 * 2cos * x

Multiply 3 * 2
1 + -6cosx = 6cos * x

Multiply cos * x
1 + -6cosx = 6cosx

Solving
1 + -6cosx = 6cosx

Solving for variable 'c'.

Move all terms containing c to the left, all other terms to the right.

Add '-6cosx' to each side of the equation.
1 + -6cosx + -6cosx = 6cosx + -6cosx

Combine like terms: -6cosx + -6cosx = -12cosx
1 + -12cosx = 6cosx + -6cosx

Combine like terms: 6cosx + -6cosx = 0
1 + -12cosx = 0

Add '-1' to each side of the equation.
1 + -1 + -12cosx = 0 + -1

Combine like terms: 1 + -1 = 0
0 + -12cosx = 0 + -1
-12cosx = 0 + -1

Combine like terms: 0 + -1 = -1
-12cosx = -1

Divide each side by '-12osx'.
c = 0.08333333333o-1s-1x-1

Simplifying
c = 0.08333333333o-1s-1x-1

See similar equations:

| 1/6t=4 | | Y=sin(4x) | | (-2/3)x^2-5 | | 5x^2+13-6=0 | | 10h+5=85 | | 19z-6(4z-1)= | | 20x^2+5.2x-0.5=0 | | 0=8-2y | | 6=2.5(w-2) | | 20x^2=1 | | 6(-6n+5)=138 | | 2r+55=6r+72r | | 8m-15=33 | | 7x+24=14 | | 13=-x/5 | | t-4=15 | | 6y=4x+7 | | y=1.5+3 | | 7(7x+8)+8= | | -51/2m=-22 | | 7z-z=-6z-3-6z | | ((sqrt(x-3))/(x-3))=0 | | Ln(5x-3)=14 | | x-1/4=20 | | (sqrt(x-3))/(x-3) | | t-9=19 | | 16-5x=6-7x | | 11=b/2 | | 9ln(4x)=63 | | (x/6a^3k)-(5ay^2/9dk^2) | | 6(3x-5)=9 | | (1/2)x^4-8=0 |

Equations solver categories